Identity and Perceptions of Procedural Justice in the Courts in Turkey: Ethnic and Political Factors - Sema Akboğa; Osman Şahin (İnsan & Toplum)
Procedural justice, which is about the fairness of procedures that the legal authorities use in their interactions with the public, is an important determinant of people’s general evaluations of these authorities. Based on a nationally representative survey with 1,804 people, this article investigates how socio-political identities such as ethnicity and one’s status as a political winner or loser affect people’s perceptions of procedural justice in the courts in Turkey. Multivariate regression analysis revealed that Kurds and political losers are more likely than Turks and political winners, respectively, to think that the courts in Turkey are not procedurally just. Furthermore, we found that voting for the incumbent party or being an Alevi does not have an effect on Kurds’ perceptions of procedural justice in the courts. We, therefore, argue that ethnicity and being a political winner are two important identity factors that determine people’s perceptions of procedural justice in the courts in Turkey. We concluded that because Kurds and political losers are less likely to identify with the state, they have more negative perceptions of procedural justice in the courts in Turkey.